"Lost in the literature." People with intellectual disabilities who identify as trans: a narrative review. Issue 1 (2nd February 2022) - Keates, Nathan; Dewar, Eleanor; Waldock, Krysia Emily
Abstract : Purpose: This narrative review aims to examine how trans people with intellectual disabilities are perceived and discussed in the academic literature. Design/methodology/approach: A narrative review was carried out to better understand the positioning of people with intellectual disabilities who identify as trans. Findings: There was a lack of clear terminology, an over medicalization of both people with intellectual disabilities and trans people and evidence that identifying with a non-conforming gender identity was seen as a problem by services. Services need to be better informed about issues around gender identity so that they are able to better support trans people with intellectual disabilities. Originality/value: To the best of the authors' knowledge, no previous literature review has focused only on trans people with intellectual disabilities.